2020
DOI: 10.1097/bsd.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

MagnetOs, Vitoss, and Novabone in a Multi-endpoint Study of Posterolateral Fusion

Abstract: Study Design: This study was a multi-endpoint analysis of bone graft substitutes implanted as a standalone graft in a clinically relevant Ovine model of instrumented posterolateral spinal fusion (PLF). Objective: The objective of this study was to obtain high-quality evidence on the efficacy of commercial bone graft substitutes compared with autograft in instrumented PLF using a state-of-the-art model with a complete range of assessment techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…They are osteoinductive. The osteoinduction is trigged either by the addition of chemical elements such silicates ions (Actifuse bone graft, by Baxter) or by tailored sub-micron surface topography and porosity [47] that has the capability to induce bone formation in ectopic or heterotopic location such in muscle or under skin. (Figures 5 and 6).…”
Section: Bone-like Calcium Phosphatesmentioning
confidence: 99%
See 2 more Smart Citations
“…They are osteoinductive. The osteoinduction is trigged either by the addition of chemical elements such silicates ions (Actifuse bone graft, by Baxter) or by tailored sub-micron surface topography and porosity [47] that has the capability to induce bone formation in ectopic or heterotopic location such in muscle or under skin. (Figures 5 and 6).…”
Section: Bone-like Calcium Phosphatesmentioning
confidence: 99%
“…AB: Autograft bone; BCP < μm, biphasic calcium phosphate with submicron topography; BG, bioglass; TCP, tricalcium phosphate. [47]. An injectable bone graft formulation and hardening injectable bone cements.…”
Section: Biocomposites: Chitosan-cap Bioceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biphasic calcium phosphate with submicron needle-shaped surface topography (BCP) investigated in this study has previously been demonstrated to be a promising solution for predictable spine fusion, circumventing the disadvantages of the gold standard autologous bone graft (ABG), i.e., limited availability, donor site morbidity, patient complications such as pain, secondary site infections, and subsequent risks of revision surgery [1][2][3][4]. In skeletally mature rabbit and sheep posterolateral fusion models, BCP showed fusion rates equivalent to ABG [5,6], and head-to-head comparison studies have shown an accelerated bone formation and superior fusion rate with needle-shaped surface topography compared to conventional grain-shaped surface topographies in dog muscle and sheep spine studies [7,8]. Recently, the first clinical case series reported successful fusion rates 12 months post-surgery near 97% (94 out of 97 levels) in the lumbar fusion cohort of 52 patients, and 93.8% (75 out of 80 levels) in the cervical fusion cohort of 25 patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their resorption rate is challenging to tailor and a foreign body reaction is occasionally observed as a consequence of their implantation [31,37,38]. Thus, the use of these bone substitutes as a stand-alone treatment is limited and currently they are mainly used as autologous graft extenders [33,39,40]. The drawbacks of autologous and allogeneic bone transplantation together with the lack of satisfactory bone substitutes represent the major driving force behind the search for alternatives.…”
Section: When Fracture Healing Fails: Clinical Problems and Available Treatmentsmentioning
confidence: 99%